Salvage Islet Auto Transplantation After Relaparatomy. Issue 10 (October 2017) - Balzano, Gianpaolo; Nano, Rita; Maffi, Paola; Mercalli, Alessia; Melzi, Raffaelli; Aleotti, Francesca; Gavazzi, Francesca; Berra, Cesare; De Cobelli, Francesco; Venturini, Massimo; Magistretti, Paola; Scavini, Marina; et al.
Abstract : Background: To assess feasibility, safety, and metabolic outcome of islet auto transplantation (IAT) in patients undergoing completion pancreatectomy because of sepsis or bleeding after pancreatic surgery. Methods: From November 2008 to October 2016, approximately 22 patients were candidates to salvage IAT during emergency relaparotomy because of postpancreatectomy sepsis (n = 11) or bleeding (n = 11). Feasibility, efficacy, and safety of salvage IAT were compared with those documented in a cohort of 36 patients who were candidate to simultaneous IAT during nonemergency preemptive completion pancreatectomy through the pancreaticoduodenectomy. Results: The percentage of candidates that received the infusion of islets was significantly lower in salvage IAT than simultaneous IAT (59.1% vs 88.9%, P = 0.008), mainly because of a higher rate of inadequate islet preparations. Even if microbial contamination of islet preparation was significantly higher in candidates to salvage IAT than in those to simultaneous IAT (78.9% vs 20%, P < 0.001), there was no evidence of a higher rate of complications related to the procedure. Median follow-up was 5.45 ± 0.52 years. Four (36%) of 11 patients reached insulin independence, 6 patients (56%) had partial graft function, and 1 patient (9%) had primary graft nonfunction. At the last follow-up visit, median fasting C-peptide was 0.43 (0.19-0.93) ng/mL; median insulin requirement was 0.38 (0.04-0.5) U/kg per day, and median HbA1c was 6.6% (5.9%-8.1%). Overall mortality, in-hospital mortality, metabolic outcome, graft survival, and insulin-free survival after salvage IAT were not different from those documented after simultaneous IAT. Conclusions: Our data demonstrate the feasibility, efficacy, and safety of salvage IAT after relaparotomy. Abstract : This cohort study demonstrates that salvage islet autotransplantation in patients undergoing emergency complete pancreatectomy is feasible, effective, safe, and comparable to that observed after elective simultaneous islet autotransplantation. Supplemental digital content is available in the text.